Pengaruh Aliran Filsafat Hukum: Aliran Hukum Alam, Positivisme Hukum, Dan Utilitarian Dalam Perkembangan Ilmu Hukum - Muhammad Aldo Savero; Aqila Husna; Ania Nasyira; Faiza Nisrina; Roselia Ariyanti (Universitas Sains dan Teknologi Komputer, 2024)
Abstract Philosophy seeks to make sense of the world by interpreting it from a very broad perspective, encompassing everything the human mind is capable of. It is different from studying law, which has a narrow scope because it only focuses on standards and regulations. The goal of philosophy is something that can be achieved by human reason. This research was conducted using the normative juridical method, namely by examining literature materials related to the influence of the school of legal philosophy in the development of legal science. This research is conducted by examining secondary legal materials in the form of journals and scientific articles related to the schools of legal philosophy and how they influence the development of legal science and the role of law in society. There are several schools that develop and influence the formation of law including: Natural Law (Justice), Positivism (Certainty), Utilitarianism (Benefit). The role of law in carrying out this concept is very important, because law is the main tool for regulating and enforcing the principles of social justice in modern society. In the development of legal awareness, the next factor affecting legal awareness is about public obedience to the law. Thus, all the interests of society will be protected and people's lives will become more peaceful. The development of legal science can be facilitated by the schools of positivism, natural law, and utilitarianism, each of which has its own characteristics. Because human behavior is unpredictable, there must be protection of individual rights and guarantees of life in society are needed to create security and safety of justice. What influences the development of legal awareness is the community's obedience to the law, and all community interests will be carried out.